International Law and Use of Force by States Outside of National Borders while Countering Terrorism: The Case of the Emerging Islamic State (ISIL) - ADU, Yao Nikez; ANANIDZE, Fridon; ALISIEVICH, Eketerina; ADU, Svetlana; ZHAROVA, Olga (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The question of the legality of the use of force by states in international relations (IR) after the adoption of the United Nations (UN) Charter in 1945 is discussed among scholars and political actors continuously. This dispute of prohibition, regulation or limitation of the use of force between states raises an important question about the use of force by States while countering terrorism or extremist groups outside national borders. The objective of this article is to analyze the nature and legality of the international use of force while countering terrorism. The authors of this scientific paper are not only trying to describe the role of the UN in combatting international terrorism such as ISIL, but also the significant role of the Security Council and its role in regulating the use of force by States to counter terrorism. The article analyzes the international practices in countering terrorism by States.